CFD simulation of a rotary compressor with gas injection. (August 2019) - Wang, Junfeng; Ding, Hui; Wang, Baolong; Ding, Yunchen; Huang, Yanfen
Abstract: Rotary compressors are widely used in small capacity refrigeration and heat pump Systems. Gas injection is an effective way to improve compressor efficiency especially when operating under low temperature. A novel design injects gas through the rotary compressor blade, controlled by a built in reed valve. CFD simulation provides valuable insights to help design engineers to verify, to analyze, and to improve the performance of compressors. For this particular application, besides modeling rotary compressor operation, CFD simulation also needs to solve reed valve dynamics with combined movement of the blade. In this paper, a full 3D transient CFD model of a rotary compressor with gas injection is described in detail. Real gas properties is used for the refrigerant. Methodology used to model reed valve dynamics is discussed. Simulation results are validated by experiment data. Effects of gas injection are evaluated by comparing the simulation results for the cases with and without gas injection.